Scapular muscles strength in college baseball players with and without a history of UCL injury - Waldhelm, A.; Flattmann, Z.; Hundley, K.; Hundley, S.; Durdunji, C.; Jones, Z.; Schwarz, N. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Ulnar collateral ligament (UCL) injuries are common in overhead athletes and have increased in prevalence among baseball pitchers of all ages. The purpose of this study was to examine the difference between the strength of five scapular stabilizing muscles in college baseball pitchers with and without a history of UCL surgery. Data on a pitcher with a recent diagnosis of a Grade I UCL sprain was also included as a case study. METHODS: Thirty-nine college baseball pitchers, eight pitchers with a history of UCL surgery, volunteered to participate. Each participant completed a self-guided warm-up and then the strength of five scapular stabilizing muscles were assessed using a hand-held dynamometer. Station one tested latissimus dorsi and serratus anterior while the middle trapezius, lower trapezius, and rhomboids were assessed at station two. To determine the difference between groups Mann-Whitney U tests were performed with a significance level of P=0.05. RESULTS: The results showed no significant difference in muscle strength for all five muscle strength tests between the two groups. Although not statistically significant, the injured group averaged greater strength than the non-injured group for all five muscles tested. CONCLUSIONS: The results of this study indicated there was no difference is scapular stabilizing muscle strength between college baseball pitchers with and without a history of UCL surgery. This may be due to proper rehabilitation and rest following the UCL injury. More research is needed to determine the role of scapular stabilizing muscle strength on elbow and UCL injury in college baseball players.